Species Characteristics of the Causative Agents of Mycosis of Horseflies - Abdusalomovna, Jamalova, Feruza (American Journal of Botany and Bioengineering, 2024)
The article discusses the etiological agents of horsefly mycoses, identified as fungus from horseflies belonging to the groups Zygomycetes and Deuteromycetes. The first group consists of 2, whereas the second ranges from 8 genera. This paper provides a detailed description of the method by which fungi affect the bodies of larvae and imago of horseflies. Equipped with a formidable piercing-sucking mechanism, horseflies, as bloodsuckers, pose a significant threat when they assault animals. When they ingest blood, they are able to detect, and then retain and transfer viruses including highly hazardous illnesses. Hence, a thorough investigation of the fauna and ecology of horseflies is necessary to safeguard human health and avoid the infestation of farm animals by these blood-sucking insects.